«Санація» прикордоння УСРР: поборювання «польсько-українського фашизму» на Поділлі 1930-ті роки - Тітова, Н. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
The present article is dedicated to repressive measures of NKVD against Ukrainian and Polish population of Eastern Podilya during 1930th. These measures were justified by the necessity to secure western border of republic against possible armed attack of «imperialistic aggressors» as well as the need to eliminate the spy network of «Polish-Ukrainian fascism» among the multi-ethnical population of the region.